Etude de la somatotypie des haltérophiles africains - Dachri, Hamid; Mimouni, Nabila (دفـاتر المـــــــــــخبـر, 2018)
ملخص: إن تطور النتائج الرياضية والذي أصبح اليوم جد صعب من أجل د فع الأرقام القياسية إلى ما بعد الحدود البيولوجية الحالية، عدة مختصين في ميدان علوم الرياضة توجه نحو دراسة العلاقة الموجودة بين قدرات تكيف الجسم مع حمولات التدريب ذات الشدة العالية مع مرفولوجية الرياضي، رغما أن هذا يعتبر غير كافي، بحيث يوجد العديد من المعايير المرفولوجية عند رباعي رفع الأثقال من المستوى العالمي، هذه المعايير لتوضح  بقدر كبير المؤشرات الحقيقة حسب الحركة والتقنية الرياضية. الهدف من هذه الدراسة هو تعريف الوجهة السوماتية لرباعي رفع الأثقال الأفارقة لمختلف الفئات الوزنية، من خلال قياس وتقييم مختلف المعايير المرفولوجية، مرفولوجية رباعي رفع الأثقال الأفارقة تعرف حسب ثلاث فئات وزنية ( خفيفة، متوسطة، ثقيلة). توضيح نتائج الدراسة السوماتية التي اطهرت أرقام متقاربة بين الرباعين الجزائريين و الأفارقة، توضيح النتائج المتقاربة والمتباعدة بين المستويين ، ربط الجانب المرفولوجي للرباع مع النتائج الرياضية المحققة. Abstract  : The evolution of sport performance became now nearly impossible to push the records more than the actual biologic limit. it pushes several specialists to think that it exists a certain ties between sciences of the sport and capacities of adaptation to loads of intensive training and the specific morphology.  This isn’t also evident, because it exists a morphological characters at weightlifters of worldwide level. These characters don't necessarily raise the most adequate indications according to the gesture or the technique.  The objective of our work is to determinate the somatotypical profile of the African weightlifters of different categories of the weight, through the morphological parameter assessment, and to situate this profile with regard to weightlifters of high level. the african weightlifters morphology define themselves according to three category of the weight (light, mean, heavy).  The somatotypy of the present Algerian weightlifters of the nearer values to the African weightlifters.  The Algerian weightlifters present the same morphological characteristic that the Arabian and African weightlifters.